2021
DOI: 10.4085/1062-6050-0121.21
|View full text |Cite
|
Sign up to set email alerts
|

High School Sports During the COVID-19 Pandemic: The Effect of Sport Participation on the Health of Adolescents

Abstract: Context: During the fall of 2020, some high schools across the US allowed their students to participate in interscholastic sports while others cancelled or postponed their sport programs due to concerns regarding COVID-19 transmission. It is unknown what effect this has had on the physical and mental health of adolescents. Objective: Identify the impact of playing a sport during the COVID-19 pandemic on the health of student athletes. Design: Cross-sectional study. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 28 publications
3
36
0
Order By: Relevance
“…Consistent with trends noted in the recent literature, the timeline of the lockdown has been associated with declining mental health of this subgroup of adolescents [ 21 , 22 , 23 , 24 , 25 , 26 ]. Given the temporal sequencing of the PHQ depression screening results among the high school students and the mandated lockdown, it is logical that the increased rate of depression observed is associated with the pandemic.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Consistent with trends noted in the recent literature, the timeline of the lockdown has been associated with declining mental health of this subgroup of adolescents [ 21 , 22 , 23 , 24 , 25 , 26 ]. Given the temporal sequencing of the PHQ depression screening results among the high school students and the mandated lockdown, it is logical that the increased rate of depression observed is associated with the pandemic.…”
Section: Discussionsupporting
confidence: 85%
“…Given that physical exercise has shown to be protective against depressive symptoms in adolescents [ 20 ], the loss of organized physical activity may have amplified the effects of the shutdown [ 21 , 22 ]. Limited studies have focused on student athletes, but research has shown the benefits of increased physical activity level, social interactions, and sports participation on overall mental health functioning [ 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the risk factors that are positively related to high anxiety in adolescents are lack of rest, having difficulty with online education, having too much schoolwork, focusing too much on graduation, where adolescents live, and low physical activity (AlAzzam et al, 2021 ; Andreas & Brunborg, 2021 ; Liu et al, 2021 ). Adolescents who participate in sports activities have a lower risk of anxiety and depression than adolescents who do not do sports (McGuine et al, 2021 ). The residence of adolescents also can increase the risk of anxiety.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, social isolation (eg, with team and tournament ‘bubbles’), concerns about well-being and financial problems, a fear of body changes with altered training and dietary regimens, as well as uncertainty about their identity, career and future, have been mentioned as COVID-19-specific mental health contributing factors 3–5 8. Loss of athlete motivation, meaning and identity may have also perpetuated depressive symptoms in athletes, especially for those exposed to competition postponement 9…”
Section: Covid-19 Specific Contributing Factorsmentioning
confidence: 99%